QUANTITATIVE ASSESSMENT OF EXPORTS OF PLANT PRODUCTS OF THE ALTAI REGION - Sergey N. Bocharov; Marina M. Butakova; Olga N. Sokolova (Siberian Journal of Life Sciences and Agriculture)
Changes in the structure of grain supplies in Europe, difficulties with logistics, as well as sanctions pressure instruments have significantly transformed the functioning mechanisms of global food markets. As a result, for food exporting regions the importance of issues related to the study of the structure and dynamics of exports, as well as assessing the prospects of certain types of products, is increasing.